The Earth : A Very Short Introduction - Redfern, Martin, 1954- (Oxford, New York Oxford University Press, 2003)
Exploring the geological research, this title explains how advances in the understanding of plate tectonics, seismology, and satellite imagery have enabled us to see the Earth for what it is. It introduces the concepts of continental drift, the earth's structure, sea floor spreading, and the relationship between the atmosphere and the oceans.
Include Illustration and Index
Keywords: Earth sciences